Seawater consumption in dehydrated hooded seals (Cystophora cristata) - Verlo, Are (Universitetet i Tromsø, 2012)
Studies based on satellite-tracking show that hooded seals (Cystophora cristata) spend many months out in the open sea each year. When the seals are out in the open sea they have no access to fresh water. Experimental studies have showed that hooded seals drink seawater and that they have the capacity to produce urine with Na+ and cl- concentrations equal to or higher than that of seawater. They may also produce urine with an osmolality twice that of seawater. This indicates that the hooded seal may use seawater to restore water balance and maintain homeostasis. The purpose of this study is to quantify the amount of seawater drunk as a result of a controlled experimental dehydration and to monitor the endocrine response to dehydration and seawater drinking. Following 24 hrs of fasting five subadult hooded seal males were dehydrated using the diuretic mannitol. They were then given al lib access to seawater for 48 hrs. For the duration of the experiment total body water and the turnover rates of water was estimated by tritiated water injections and subsequently isotope dilution. Plasma parameters such as Na+, Cl- were monitored and all seals maintained relatively stable plasma concentrations of the electrolytes for the duration of the entire experiment, while urinary excretion of Na+ and cl- increased after ad lib access to seawater. Plasma osmolality and hematocrit values indicated seawater intake. The amount of seawater drunk by the seals were calculated as the difference between total influx and water influx from respiration and endogenous reserves. The hooded seals drank on average 1900 ml of seawater each day. The role of the hormones ,ADH and aldoesterone ,in the osmoregualtion of hooded seals still remain somewhat unclear.